Components decoder of complex channel with orthogonal carriers frequency division - Бєлов, Володимир Сергійович; Бєлов, Антон Сергійович (Eastern-European Journal of Enterprise Technologies, 2013)
There had been presented the result of processing elementary components obtained from the multiplexed signals with Orthogonal Frequency-Division Multiplexing (OFDM), with the analysis of states of these components at particular times and there had also been analyzed their influence on a quality of the Group Signal. There had been determined that unconditional signal analysis parameter is a value that allows in conjunction with frequency diversity and the number of subcarriers specify the location of subcarriers on the frequency axis. Mathematically there had been analyzed signals of the complex channel with OFDM, with the consideration of the autocorrelation function. There had also been determined the properties of the signals with QPSK modulation, based on the encoding of two bits of information transmitted by one symbol. In this way, the symbol rate is twice less then the information rate. There had also been determined the properties of the signals with QAM, and the information parameter is a change of both, amplitude and phase, which significantly increases the information capacity of the channel and increases the interference immunity of the system. There had been determined the properties of the signals with Frequency-Shift Keying (FSK), and Minimum Shift Keying (MSK), which are most commonly used in the modern digital communications, due to their generation (detection) simplicity, and insensitivity to the initial phase, but having uneconomic spectrum consumption for OFDM. There had been developed a block diagram of the components decoder.